Investigation of bacterial contents from persistent endodontic infection and evaluation of their inflammatory potential - Cardoso, Flï¿½via Goulart Da Rosa [UNESP]; Chung, Adriana [UNESP]; Martinho, Frederico Canato [UNESP]; Camargo, Carlos Henrique Ribeiro [UNESP]; Carvalho, Claudio Antï¿½nio Talge [UNESP]; Gomes, Brenda Paula Figueiredo De Almeida; Valera, Marcia Carneiro [UNESP] (FapUNIFESP (SciELO), 2016)
This clinical study investigated and quantified cultivable bacteria and their levels of endotoxins in persistent endodontic infection, determining their antigenicity against macrophages and fibroblast cells by IL-1β and TNF-α secretion and evaluating their relationship with clinical and radiographic features. Samples from the root canals were obtained after root filling removal. Culture techniques were used to determine the bacterial count and the endotoxins were determined by LAL-assay. PCR analysis (16S rDNA) was used for bacterial detection. Raw 264.5 macrophages and V79 fibroblast were stimulated with endodontic contents. ELISA assay measured the amounts of IL-1ï¿½/TNF- □secretion. Bacteria and endotoxin medians were 1.24x105 CFU/mL and 9.62 EU/mL, respectively. Porphyromonas endodontalis was the most frequently detected species. Higher levels of endotoxins were found in teeth with pain on palpation (23.56 EU/mL) rather than in its absence (8.21 EU/mL). Larger areas of bone destruction were related to higher levels of endotoxins and IL-1β and TNF-α secretion. The study findings revealed the presence of Gram-negative bacteria species in persistent endodontic infection, with their endotoxins related to both severity of bone destruction and development of symptomatology. Moreover, larger areas of bone destruction were related to higher levels of IL-1β and TNF-α secreted by macrophages and fibroblast cells.
Keywords: Bacteria; Cytokines; Endodontic infection; Endotoxin; Root canals